2011
DOI: 10.3386/w17070
|View full text |Cite
|
Sign up to set email alerts
|

The Doctor Might See You Now: The Supply Side Effects of Public Health Insurance Expansions

Abstract: In the United States, public health insurance programs cover over 90 million individuals. Changes in the scope of these programs, such as the Medicaid expansions under the recently passed Patient Protection and Affordable Care Act, may have large effects on physician behavior. This study finds that following the implementation of the State Children's Health Insurance Program, physicians decreased the number of hours spent with patients, but increased their participation in the expanded program. Suggestive evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…3 Garthwaite (2012) Massachusetts reform led to shorter hospital stays. Kondo and Shigeoka (2013) found that hospitals increased their capacity (as measured by number of beds) after the introduction of universal health insurance in Japan, but there were no noteworthy changes in the numbers of medical institutions, physicians, or nurses.…”
Section: Introductionmentioning
confidence: 99%
“…3 Garthwaite (2012) Massachusetts reform led to shorter hospital stays. Kondo and Shigeoka (2013) found that hospitals increased their capacity (as measured by number of beds) after the introduction of universal health insurance in Japan, but there were no noteworthy changes in the numbers of medical institutions, physicians, or nurses.…”
Section: Introductionmentioning
confidence: 99%
“…When trying to accommodate higher demand by increasing volume, physicians can change treatment intensity and decrease their work per patient. While this increases volume and the number of patients that the physician treats, it may also raise quality of care concerns if the previous treatment intensity was optimal from the payer or patient perspective (Garthwaite, 2012;McDonald et al, 1974). On the other hand, studies have shown that physicians might simply work longer hours to see more patients without changing treatment intensity or expand health care supply through a broader use of nurse practitioners, physician assistants, or other providers (Kaiser Family Foundation, 2013).…”
Section: Physician Responses To the Coverage Expansionmentioning
confidence: 99%
“…Depending on the marginal revenue of seeing patients insured through higher reimbursement rates (e.g., privately insured), physicians may reduce their caseload or stop treating patients with lower relative payments, such as those insured by TRICARE or Medicaid (Kemp, 2012). Indeed, data show that despite increases in both Medicaid payment rates and its enrollment over the previous decade and some evidence on increased access to care (Baker and Royalty, 1997;Garthwaite, 2012), the share of physicians accepting Medicaid patients had decreased (Cunningham and May, 2006). 1 Several studies have shown, however, that low or nonparticipation rates varied spatially, as they are associated with such factors as the size of the Medicaideligible population in the geographic area (Mitchell, 1991) and other community-level characteristics, such as income per capita (Perloff et al, 1997).…”
Section: Physician Responses To the Coverage Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 We follow papers such as Currie and Gruber (2001), DeLeire, Lopoo, andGarthwaite (2012) in estimating the reduced-form effect of simulated Medicaid eligibility. In the spirit of Currie and Gruber (1996), we have also estimated instrumental variable regressions in which we instrument for the actual fraction of CPS respondents eligible for Medicaid with the simulated fraction eligible for Medicaid.…”
Section: Graphical Evidence and Aggregate-level Analysesmentioning
confidence: 99%